2020
DOI: 10.31729/jnma.4882
|View full text |Cite
|
Sign up to set email alerts
|

Selected Risk Factors and Pattern of Semen Abnormality in Male Partners of Infertile Couples in Eastern Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Semen analysis is an initial basic step in evaluating and diagnosing male infertility. Multiple risks factors in combination or alone are responsible for abnormal semen parameters. The present study aimed to study certain risk factors and semen parameters of infertile male. Methods: It was a descriptive cross-sectional study. We consecutively enrolled 186 male partners of infertile couple who underwent certain risk factors evaluation and semen analysis according to WHO guideline. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
4
4
0
Order By: Relevance
“…11.1% in Italy [27], and only 3.2% in a recent study in Germany [28]. The rate of seminal infection in infertile men close to the rate of our study has been reported form Nepal [23,29]. The presence of bacteria in semen in a signi cant number may be an indicator of male accessory gland infection or male genital tract infection [30,31].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…11.1% in Italy [27], and only 3.2% in a recent study in Germany [28]. The rate of seminal infection in infertile men close to the rate of our study has been reported form Nepal [23,29]. The presence of bacteria in semen in a signi cant number may be an indicator of male accessory gland infection or male genital tract infection [30,31].…”
Section: Discussionsupporting
confidence: 81%
“…Abnormality in semen based on the same seminal characteristics was reported to be 44% [22] and 66.2% [18] from two different hospitals of Nepal, which correlates our study with the semen abnormality trend of other studies among the Nepalese population. The most common characteristic in this study was teratozoopermia as with previous studies [14,23]. However, asthenozoospermia [22,24], and oligozoospermia [16] were also found to be the most common semen characteristics in Nepal.…”
Section: Discussionsupporting
confidence: 77%
“…Evaluation and diagnosis for primary infertility in men often begin with semen analysis [ 17 ] especially as certain semen parameters are linked to the functional competence of the sperm cells [ 18 ]. Our findings showed that the herbal formulation caused a significant increase in the sperm count of the experimental rats.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is classified as normal, following the opinion of Kumar and Singh (2015) which states that in most ejaculation the percentage of abnormal spermatozoa ranges from 5-20%. Pokhrel et al (2020) stated that if abnormal spermatozoa are more than 25% of the total spermatozoa in one ejaculation, it will reduce fertility. Meanwhile, according to Rengan et al (2012), spermatozoa abnormalities that exceed 14% indicate the presence of symptoms of infertility or infertility in a male, whereas according to Kumar and Singh (2015), abnormal sperm counts in semen up to 20% will not cause a decrease in fertility rates.…”
Section: Abnormality Of Muscovy Duck Semenmentioning
confidence: 99%